Post-Burn Sceptic Limb in Epileptic Sudani Young Man - Khan, Abdul Waheed; Hassan Jaffar; Tarique Ahmad Maka (Pakistan Armed Forces Medical Journal, 2023)
Burns in epileptic patients are not uncommon, but it is difficult to manage in remote areas of third-world countries. Despite the reduction in burn injuries secondary to a seizure, such injuries still lead to significant morbidity and mortality. In Darfur, Sudan, we managed such an epileptic patient having a full-thickness burn endangering the limb and life. Since these patients should adhere to a specific medication, controlling it remains to be difficult. The patient was managed with serial debridement, dressings, antibiotics, anti-epileptics and a protein diet. Therefore, preparation for preventive strategies consists of lifestyle modification and patient education that is further warranted.